The Phenomenon of Boarding School and Its Mathematics Learning - Hendrayana, Aan; Mutaqin, Anwar; Syamsuri, Syamsuri (Al-Jabar: Jurnal Pendidikan Matematika, 2019)
The phenomenon of boarding school has evolved since the 1990s. In addition to having advantages, the school also has barriers in the learning process. Therefore, the need to explore some information directly related to the reasons why boarding school is developed, students’ life in school together and the learning process that occurred. The research method is used  a qualitative approach. Schools in this study are limited to Islamic boarding schools at junior high school level in grade VII. The research procedure is undertaken to find the phenomenon of research subjects that occurred at boarding schools. The validity of data in this research uses source and method triangulation techniques, namely by checking phenomena obtained from observations, interviews with parents, interviews with students, interviews with teachers, and interviews with teachers dormitories. The general conclusion regarding Islamic-based boarding schools is that the school has become the choice of parents in educating their children to gain abilities in the religious and academic fields. In mathematics learning, the teachers prefer direct approach learning rather than indirect learning, and also most of them do not use a lesson plan as teaching guides. Therefore, the school must be able to choose and apply a learning approach oriented to the conditions of diversity that occur in boarding schools so that students have no difficulty in receiving the subject matter.